2012
DOI: 10.1001/archsurg.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Routine Same-Day Discharge After Acute or Interval Appendectomy in Children

Abstract: Hypothesis:The outcomes of and parental satisfaction with same-day discharge in children undergoing laparoscopic appendectomy warrant making it the usual and customary pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 15 publications
0
38
1
2
Order By: Relevance
“…The more predictable post‐operative course for uncomplicated appendicitis is amenable to an expedited clinical pathway. Some protocols enabled routine same‐day discharge . pLOS in these cohorts is more often reported in hours rather than days; Halter et al and Alkhoury et al reported the shortest mean pLOS, being 2.5 (±1.26, range 1–5.5) hours and 4.8 (±2.1, range 1–12) hours respectively .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The more predictable post‐operative course for uncomplicated appendicitis is amenable to an expedited clinical pathway. Some protocols enabled routine same‐day discharge . pLOS in these cohorts is more often reported in hours rather than days; Halter et al and Alkhoury et al reported the shortest mean pLOS, being 2.5 (±1.26, range 1–5.5) hours and 4.8 (±2.1, range 1–12) hours respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic selection and dosage were key protocol components in most studies, but there is continuing disparity and debate regarding antibiotic selection (Table S1). Some favour monotherapy with piperacillin‐tazobactam, cefmetazole or cefoxitin, while others prefer multi‐agent therapy with combinations such as ceftriaxone and metronidazole . Many protocols focussed efforts on rationalizing post‐operative antibiotic duration of therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors feel that appendicectomy is an outpatient operation. 11 Others consider appendicectomy unnecessary in many cases. 12 As surgeons grapple with these paradigm shifts, it is valuable to review the history of appendicectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, along with advances in endoscopic surgery, LA was first described as an optional technique for removing the appendix. LA can be performed using one or more laparoscopy ports [7,8].…”
Section: Introductionmentioning
confidence: 99%